TRADISI MUJĀHADAH TAḤFĪẒ AL-QUR’ĀN DI PONDOK PESANTREN AL-ITTIFAQIAH INDRALAYA OGAN ILIR SUMATERA SELATAN (Analisis Living Qur’an) - Amin Muhammad (Dirosat : Journal of Islamic Studies, 2017)
Mujāhadah taḥfīẓ al-Qur’ān is a big effort of santri in Al-Ittifaqiah Islamic Boarding School to fixing their memorization of the quran. Mujāhadah is consisting three levels, namely firts mujāhadah or mujāhadah ūlā, second mujāhadah or mujāhadah ṡāniah, and third mujāhadah or mujāhadah ṡāliṡah (also known by mujāhadah majlīs asy-syahādah). The author uses living Quranic analysis to examine the historicity and sosial construction of the tradition. The historicity of this tradition comes from the actions of the Prophet and his companions who used to recite the Quran with a certain time limit, although there is a mistake in the line of Ittifaqiah’s sanad. The Social construction of this tradition devides in three phases, namely: the externalization of the PP. An-Nur’s alumni in formulating the memorizing rules in LEMTATIQI and being objectified in LEMTATIQI’S code of conduct in chapter 1 verse 12, and being internalized by all ittifaqiah’s community.